2022
DOI: 10.1021/acs.nanolett.2c03032
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Conductive Self-Healing Nanoporous Materials Based on Hydrogen-Bonded Organic Frameworks

Abstract: Hydrogen-bonded organic frameworks (HOFs) are a class of nanoporous crystalline materials formed by the assembly of organic building blocks that are held together by a network of hydrogen-bonding interactions. Herein, we show that the dynamic and responsive nature of these hydrogen-bonding interactions endows HOFs with a host of unique physical properties that combine ultraflexibility, high thermal conductivities, and the ability to “self-heal”. Our systematic atomistic simulations reveal that their unique mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…[13][14][15] While retaining their crystalline nanoporous structures, HOFs offer several intriguing advantages over other framework materials, including low cost, [16] easy purification, [17] and the ability to heal through simple recrystallization. [18] HOFs are usually highlighted for their use in gas separation, [19][20][21][22] catalysis, [23,24] and energy storage. [25,26] In contrast, the unique potential of HOFs for applications in electronic devices is still in its early stages and demands further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] While retaining their crystalline nanoporous structures, HOFs offer several intriguing advantages over other framework materials, including low cost, [16] easy purification, [17] and the ability to heal through simple recrystallization. [18] HOFs are usually highlighted for their use in gas separation, [19][20][21][22] catalysis, [23,24] and energy storage. [25,26] In contrast, the unique potential of HOFs for applications in electronic devices is still in its early stages and demands further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen-bonded organic frameworks (HOFs) are a novel class of porous materials composed of organic units by hydrogen-bond interaction. 21 HOFs are widely applied in catalysis, biomedicine, and optoelectronic materials 22 and have been applied for the detection of glutathione, isocarbophos, and microRNA 23,24 because of distinct advantages of easy synthesis, easy-to-make film, good biocompatibility, low biotoxicity, and good flexibility. 25 To the best of our knowledge, the ECL behavior of HOFs with dissolved O 2 as a co-reactant has not been explored so far.…”
mentioning
confidence: 99%
“…In this regard, porous coordination polymers such as metal-organic frameworks (MOFs) and covalent-organic frameworks (COFs) have shown great promise as multifunctional, designer materials that can combine several unrivaled physical properties in one material system. 1,[10][11][12][13][14][15][16][17] For example, Evans et al 1 have recently demonstrated Fig. 1 Comparison of thermal conductivity as a function of elastic modulus for a wide range of materials at room temperature.…”
mentioning
confidence: 99%
“…In this regard, porous coordination polymers such as metal–organic frameworks (MOFs) and covalent-organic frameworks (COFs) have shown great promise as multifunctional, designer materials that can combine several unrivaled physical properties in one material system. 1,10–17 For example, Evans et al 1 have recently demonstrated that boronate ester-linked 2D COF thin films are endowed with low dielectric constants and possess a room temperature thermal conductivity of ∼1 W m −1 K −1 (Fig. 1) along the laminar pores, marking a new paradigm in materials design that combines relatively high thermal conductivity with low mass density.…”
mentioning
confidence: 99%